Advances in visual computing : 14th International Symposium on Visual Computing, ISVC 2019, Lake Tahoe, NV, USA, October 7-9, 2019, Proceedings.: 14th International Symposium on Visual Computing, ISVC 2019, Lake Tahoe, NV, USA, October 7-9, 2019, Proceedings. Part II (2019) - Unknown
No abstract available